Teacher learning in Vietnam - Nguyen, Huong T. M. (2015)
In order for Vietnam to seek better international integration into an increasingly globalised world, the Vietnamese government has launched educational reforms, requiring teachers to adopt ‘western’ constructivist pedagogies. This study focuses on pre-service teachers’ learning in Vietnam, where traditional attitudes towards teachers’ and learners’ roles promote passivity amongst students and unquestioning respect for the authority of teachers’ knowledge. The thesis describes a cycle of action research conducted in a major teacher training institution in Vietnam. Through an intervention based on constructivist theories, the researcher set out to investigate factors that enhance teacher learning, and barriers that hinder it, with the aim of contributing evidence to discussions about the most appropriate strategies to be employed to bring about a change for the better in teacher education. The research highlights the importance of Vietnamese teacher educators in promoting change in Vietnam.